The Contribution of Conformity and Self-Acceptance to the Development of Students' Social Skills - Diah Ayu Anggraeni; Kusnarto Kurniawan (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2022)
Low social skills are still one of the problems students face, which adversely impacts their attitude towards someone. Preliminary research showed that Junior High School students' lack of social skills is still a significant problem that needs to be resolved. Therefore, this research aims to determine the level of social skills, conformity, and self-acceptance in junior high school students and the relationship between them. The population in this study were 536 junior high students and 205 students participated as participants which recruited using the proportionate stratified sampling method. The data was collected using psychological scale specifically the social skills, conformity, and self-acceptance scale. The data collected were analyzed using the multiple regression analysis using the SPSS program. The result showed a positive relationship between conformity and self-acceptance with social skills in junior high school students. Good social skills make students complete tasks faster and more proficient in social life.